Analisis Kekuatan Komposit Laminat Hybrid Jute E-Glass Berdasarkan Pola Kerusakan dengan Metode Split Tensile Test - Rizal Afandi Purba; Achmad Jusuf Zulfikar; Iswandi Iswandi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
Research on composite materials continues to experience significant development in line with human needs for products that are lighter, stronger, easier to form, environmentally friendly, and low cost. Alternative materials sourced from natural materials such as the Jute plant combined with synthetic e-glass materials are a top priority to achieve the target of materials that are strong but environmentally friendly. In this study, the investigation aimed to analyze the effect of applying hybrid laminated composite materials of woven jute fiber sheets and e-glass (KLHJG) to cylindrical column concrete by calculating the percentage of the crack pattern (PPR) that occurs and then comparing it to the split tensile strength (KTB). ) to get the phenomenon that occurs. Specimens were printed using the ASTM D496 standard for splitting tensile strength testing. PPR is calculated using the Histogram method with the help of Adobe Photoshop software. The result obtained is that the provision of KLHJG on cylindrical column concrete can reduce PPR to below 20%. However, the JGJG composition obtained a PPR greater than 30% which indicates that this composition is not very effective in protecting the concrete structure against the external load it is subjected to.